Use of nonsteroidal anti-inflammatory drugs predicts improved patient survival for PIK3CA -altered head and neck cancer - Hedberg, Matthew L.; Peyser, Noah D.; Bauman, Julie E.; Gooding, William E.; Li, Hua; Bhola, Neil E.; Zhu, Tian Ran; Zeng, Yan; Brand, Toni M.; Kim, Mi-Ok; Jordan, Richard C.K.; VandenBerg, Scott; et al. (The Journal of experimental medicine, 2019)
PIK3CA is the most commonly altered oncogene in head and neck squamous cell carcinoma (HNSCC). We evaluated the impact of nonsteroidal anti-inflammatory drugs (NSAIDs) on survival in a PIK3CA-characterized cohort of 266 HNSCC patients and explored the mechanism in relevant preclinical models including patient-derived xenografts. Among subjects with PIK3CA mutations or amplification, regular NSAID use (≥6 mo) conferred markedly prolonged disease-specific survival (DSS; hazard ratio 0.23, P = 0.0032, 95% CI 0.09–0.62) and overall survival (OS; hazard ratio 0.31, P = 0.0043, 95% CI 0.14–0.69) compared with nonregular NSAID users. For PIK3CA-altered HNSCC, predicted 5-yr DSS was 72% for NSAID users and 25% for nonusers; predicted 5-yr OS was 78% for regular NSAID users and 45% for nonregular users. PIK3CA mutation predicted sensitivity to NSAIDs in preclinical models in association with increased systemic PGE2 production. These findings uncover a biologically plausible rationale to implement NSAID therapy in PIK3CA-altered HNSCC.